Reduced red blood cell deformability in Plasmodium knowlesi malaria - Barber, Bridget E.; Russell, Bruce; Grigg, Matthew J.; Zhang, Rou; William, Timothy; Amir, Amirah; Lau, Yee Ling; Chatfield, Mark D.; Dondorp, Arjen M.; Anstey, Nicholas M.; Yeo, Tsin W. (American Society of Hematology, 2018)
The simian parasite Plasmodium knowlesi can cause severe and fatal human malaria. However, little is known about the pathogenesis of this disease. In falciparum malaria, reduced red blood cell deformability (RBC-D) contributes to microvascular obstruction and impaired organ perfusion. In P knowlesi infection, impaired microcirculatory flow has been observed in Macaca mulatta (rhesus macaques), unnatural hosts who develop severe and fatal disease. However, RBC-D has not been measured in human infection or in the natural host M fascicularis (long-tailed macaques). Using ektacytometry, we measured RBC-D in adults with severe and non-severe knowlesi and falciparum malaria and in healthy controls. In addition, we used micropipette aspiration to determine the relative stiffness of infected RBCs (iRBCs) and uninfected RBCs (uRBCs) in P knowlesi-infected humans and M fascicularis Ektacytometry demonstrated that RBC-D overall was reduced in human knowlesi malaria in proportion to disease severity, and in severe knowlesi malaria, it was comparable to that of severe falciparum malaria. RBC-D correlated inversely with parasitemia and lactate in knowlesi malaria and HRP2 in falciparum malaria, and it correlated with hemoglobin nadir in knowlesi malaria. Micropipette aspiration confirmed that in humans, P knowlesi infection increased stiffness of both iRBCs and uRBCs, with the latter mostly the result of echinocytosis. In contrast, in the natural host M fascicularis, echinocyte formation was not observed, and the RBC-D of uRBCs was unaffected. In unnatural primate hosts of P knowlesi, including humans, reduced deformability of iRBCs and uRBCs may represent a key pathogenic mechanism leading to microvascular accumulation, impaired organ perfusion, and anemia.